Guanine crystal formation by bacteria - Pavan, María Elisa (2023)
Background: Guanine crystals are organic biogenic crystals found in many organisms. Due to their exceptionally high refractive index, they contribute to structural color and are responsible for the reflective effect in the skin and visual organs in animals such as fish, reptiles, and spiders. Occurrence of these crystals in animals has been known for many years, and they have also been observed in eukaryotic microorganisms, but not in prokaryotes. Results: In this work, we report the discovery of extracellular crystals formed by bacteria and reveal that they are composed of guanine monohydrate. This composition differs from that of biogenic guanine crystals found in other organisms, mostly composed of β anhydrous guanine. We demonstrate the formation of these crystals by Aeromonas and other bacteria and investigate the metabolic traits related to their synthesis. In all cases studied, the presence of the bacterial guanine crystals correlates with the absence of guanine deaminase, which could lead to guanine accumulation providing the substrate for crystal formation. Conclusions: Our finding of the hitherto unknown guanine crystal occurrence in prokaryotes extends the range of organisms that produce these crystals to a new domain of life. Bacteria constitute a novel and more accessible model to study the process of guanine crystal formation and assembly. This discovery opens countless chemical and biological questions, including those about the functional and adaptive significance of their production in these microorganisms. It also paves the road for the development of simple and convenient processes to obtain biogenic guanine crystals for diverse applications.